Haemocin, the bacteriocin produced by Haemophilus influenzae: species distribution and role in colonization. - LiPuma, J J (1990)
Four hundred thirty-eight strains of Haemophilus influenzae were examined for production of and sensitivity to haemocin, a bacteriocin produced by some members of this species. Whereas 199 of 212 (94%) type b isolates produced haemocin, 131 of 134 (98%) nontypeable and 91 of 92 (99%) encapsulated non-type b isolates were sensitive to haemocin. Among strains previously genetically characterized by multilocus enzyme electrophoresis, haemocin production was detected in type b isolates belonging to 25 of 29 (86%) clonally distinct electrophoretic types. None of 60 clonally distinct nontypeable strains produced this substance, and all were sensitive to it in vitro. The genes encoding haemocin production were transformed independently of the genes necessary for capsule expression from a prototypic type b strain to a nontypeable strain. After intranasal inoculation of infant rats with an equal mixture of a non-haemocin-producing strain and its haemocin-producing transformant, organisms capable of haemocin production predominated in both nasopharyngeal and blood cultures. These data demonstrate that haemocin production is strongly associated with type b encapsulated members of this species and suggest a mechanism by which haemocin might play a role in host nasopharyngeal colonization by this pathogen.